2016
DOI: 10.1038/ng.3662
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplex structures mark human regulatory chromatin

Abstract: G-quadruplex (G4) structural motifs have been linked to transcription, replication and genome instability and are implicated in cancer and other diseases. However, it is crucial to demonstrate the bona fide formation of G4 structures within an endogenous chromatin context. Herein we address this through the development of G4 ChIP-seq, an antibody-based G4 chromatin immunoprecipitation and high-throughput sequencing approach. We find ∼10,000 G4 structures in human chromatin, predominantly in regulatory, nucleos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

50
849
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 770 publications
(957 citation statements)
references
References 64 publications
50
849
1
1
Order By: Relevance
“…These control experiments do not rule out all sequence context effects or the role of all protein activators and repressors but they do provide strong support for this sequence to adopt a G-quadruplex fold to induce the gene. The observation of transcriptional activation by G4 formation in the present study is consistent with a recent demonstration that these folds in promoters up-regulate transcription on the basis of G-quadruplex ChIP-Seq in tandem with RNA-Seq analysis (9).…”
Section: Significancesupporting
confidence: 80%
See 1 more Smart Citation
“…These control experiments do not rule out all sequence context effects or the role of all protein activators and repressors but they do provide strong support for this sequence to adopt a G-quadruplex fold to induce the gene. The observation of transcriptional activation by G4 formation in the present study is consistent with a recent demonstration that these folds in promoters up-regulate transcription on the basis of G-quadruplex ChIP-Seq in tandem with RNA-Seq analysis (9).…”
Section: Significancesupporting
confidence: 80%
“…One gene in particular is vascular endothelial growth factor (VEGF), for which OG was found in the G-rich potential G-quadruplex sequence (PQS) (7) demonstrated to be responsible for transcriptional regulation of the gene (8). Strong cellular evidence for enhancement of transcription via folding of promoter G-quadruplexes was recently demonstrated by the Balasubramanian laboratory (9). Therefore, we hypothesize formation of OG in the VEGF PQS under oxidative stress conditions functions as a signaling mark to unmask the G-quadruplex fold, thus leading to transcriptional activation.…”
mentioning
confidence: 99%
“…83 It was revealed that these G4 sequences were especially present in non-nucleosomal regions in the genome and that they would enrich in promoter regions of genes. Promoter G4s occur once per promoter region and although small in size, they…”
Section: Promoter G4smentioning
confidence: 99%
“…Non-Watson-Crick secondary structures of nucleic acids, and in particular, G4 structures in DNA is an area of extremely active research (12)(13)(14)(15)(16). Although G4 structures were initially described in the context of telomeres, recent genomic data revealed tens of thousands of sequences throughout the genome (14,17) that, in principle, could form G4 structures, called potential G-quadruplex-forming sequences (PQS).…”
mentioning
confidence: 99%
“…Although G4 structures were initially described in the context of telomeres, recent genomic data revealed tens of thousands of sequences throughout the genome (14,17) that, in principle, could form G4 structures, called potential G-quadruplex-forming sequences (PQS). Many of these sequences, when folded as G4s, can bind with high-affinity cellular proteins or transcription factors (16), but the relevance and physiological role of such interactions are still actively investigated.…”
mentioning
confidence: 99%